Effect of Mobile Usage and Compromise of Rem and Non Rem Sleep Among Medical Students - Ghulam Hassan, Nauman, Iqra Akram (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to determine the effect of late night mobile usage and compromise of rapid eye movement (REM) and non-REM among medical students. Study Design: Cross-sectional study Place and Duration: Sughra Shafi Medical Complex Narowal. Jun 2021-Dec 2021 Methods: There were 170 medical students of both genders had age 19-35 years were presented in this research. After obtaining written informed consent, participants’ age, sex, BMI, and place of residence were recorded in detail. Participants filled out the Pittsburgh Sleep Quality Index (PSQI) and a validated semi-structured questionnaire that included demographic information and cellular phone data. Outcomes were assessed among patients with REM and non REM sleep. SPSS 22.0 was used to analyze all data. Results: Among 170 presented students, majority was females 97 (57.1%) and rest of the patients was males 73 (42.9%). We found that 70 (41.2%) had age 19-25 years, 60 (35.3%) had age 26-30 years and 40 (13.5%) had age 31-35 years. 120 (70.6%) had BMI <25kg/m2 and 50 (29.4%) had BMI >25kg/m2. 94 (55.3%) cases had REM sleep and 76 (44.7%) were non REM sleep. Majority of the cases were had mobile usage >4hours found in 80 (47.1%) students. There was a statistically significant (P <0.05) increase in sleep latency, decrease in sleep length, increase in inefficiency during sleep, and increase in daytime sleep disruptions in REM patients. Sleep quality was negatively connected with unawareness of night shift mode and lying posture while using a phone before bed (P <0.05). We found higher number of fatigue, headache, temper and burning eyes among REM cases as compared to non REM. Conclusion: We concluded in this study that mobile usage among patients with REM sleep resulted higher number of poor sleep quality, fatigue and headache as compared to non REM cases. The detrimental effects of late-night screen time on sleep and health should be highly publicized. Keywords: REM, Medical Students, Mobile Usage, Sleep Quality